Spatial distribution, burrow depth and temperature: implications for the sexual strategies in two Allocosa wolf spiders - Aisenberg, Anita (2011)
Allocosa brasiliensis and Allocosa alticeps are two burrowing wolf spiders that inhabit Uruguayan sandy coasts. Male efficient digging is necessary because copulation and oviposition occur inside their burrows. We examined burrow distribution, density and temperature variation according to burrow depth. Adult burrows were more frequent at the slope of sand-dunes in A. alticeps and at the base in A. brasiliensis. The base provides better digging conditions, whereas A. alticeps adults could prefer the slope to avoid intra-guild predation. Temperature buffering increased with depth, providing thermal stability in such a harsh environment as coastal dunes.